Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1109/tiv.2022.3224679
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Driving of General Mixed Platoons With CAVs and HDVs

Abstract: Eco-driving has been widely investigated over the last decade, but most studies focused on an individual vehicle or a vehicle platoon consisting of pure connected and automated vehicles (CAVs). Recently, mixed vehicle platoons consisting of both CAVs and human-driven vehicles (HDVs) have attracted much interest, considering the fact that HDVs will mix with CAVs in the traffic system for a long period. This paper proposes an eco-driving strategy for mixed platoons, composing of both offline planning and online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The HV parameters are h s = 5 m, h g = 50 m, v max = 40 m/s, τ = 0.7 s, α = 0.2, and β = 0.4. The initial vehicle state (p i , v i , a i ), i ∈ [1,3], are randomly set as: (45, 20, 0), (20,15,0) and (0, 20, 0), respectively. The sampling time, number of data samples, desired inter-vehicular distance and velocity profile are the same as Case 1.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HV parameters are h s = 5 m, h g = 50 m, v max = 40 m/s, τ = 0.7 s, α = 0.2, and β = 0.4. The initial vehicle state (p i , v i , a i ), i ∈ [1,3], are randomly set as: (45, 20, 0), (20,15,0) and (0, 20, 0), respectively. The sampling time, number of data samples, desired inter-vehicular distance and velocity profile are the same as Case 1.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Vehicle platoon refers to a convoy of vehicles that travel at the same (longitudinal) velocity whilst maintaining a desired inter-vehicular distance. Previous studies [1]- [3] revealed that vehicle platoons have a great potential in reducing traffic congestion, accidents and fuel consumption. An effective control strategy is the key to establish vehicle platoons and has attracted much research attention.…”
Section: Introductionmentioning
confidence: 99%
“…Each platoon is required to be led by a CAV. All CAVs must be positioned ahead of each HV within the platoon [27]. However, under low MPR, platoon formation is not always achievable.…”
Section: Introductionmentioning
confidence: 99%